ENHANCING STUDENTS WRITING SKILLS OF NARATIVE TEXT THROUGH TRANSITION-ACTION-DETAILS - afief fakhruddin (Journal of English Language Learning, 2021)
The aimed of this research was to explain how the use of the Transition-Action-Details Strategy enhance students’ writing skills in narative text in creating the story. It was to explain how the TAD enhance students writing skills in narative text dealing with the organization of writing. Research design was classroom action research. The data for this study were gained through test, and observation, and the respondents were four semester students who used TAD activity. The study revealed that that TAD Strategy enhance students’ writing skill in narrative text Text. The students’ means score in cycle two test was (78.99). the result was much better than  cycle  one (67.94). Based on the result above it can  be concluded that TAD could enhance sudents writing narative text.